Answer :

To Prove

RHS = 6





LHS = 3 + 1 + 2 = 6


LHS = RHS


Hence, proved.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If A + B + C = π,RS Aggarwal - Mathematics

If A + B + C = π,RS Aggarwal - Mathematics